Awareness of UiTM lecturers on gold saving / Nurul Syahmin Hanis Muhamad Syafek - Muhamad Syafek, Nurul Syahmin Hanis (2022)
People who save money are better equipped to withstand economic shocks like losing their job, create assets for the future, and are less reliant on credit to cover unforeseen needs. Gold savings can be divided into two categories: jewellery gold savings and investment gold savings. It can now be seen that gold savings can be made in a variety of ways, including purchasing gold jewellery in gold shops and storing it at home before mortgaging it when cash is needed. Due to uprising variety of ways to save gold there still a weak involvement Malaysian citizens towards gold saving, this study attempts to identify what is UiTM lecturer understanding on the basic concept of gold saving, what is their opinion on factors that influence UiTM lecturer making gold saving and also what is their one personal factors influencing them to saving gold. More over this study also aims to analyse what UiTM lecturers understand and awareness toward the concept of shariah gold saving product and lastly aims to know what is their preferences on saving methods: cash or gold. Structured interviews were conducted to 4 UiTM lecturer via google meet session and WhatsApp voice over. This study shows that there still a weak understanding Of UiTM lecturers on the understanding of gold saving concept and this make the participant of UiTM lecturer on making gold saving is less. Moreover, level of income also effected in influencing them to make gold saving. This study concludes that knowledge on gold saving is important in order to make sure they interested in making gold saving, but the level of income also must strength in order to make sure they have side income to saving gold.